Resources for oral health in Africa - Foláyan, Moréniké Oluwátóyìn; Bhayat, Ahmed; Mikhail, Sara S.; Ndembi, Nicaise; El Tantawi, Maha (Frontiers in Oral Health, 2025)
Oral health in Africa is often overlooked despite its substantial impact on overall health and well-being. Currently, Africa has a very high prevalence of dental diseases, including untreated dental caries in permanent teeth, severe periodontal disease and oral cancer. Dental human resources are also very low, with dentists ranging from 1.77 to 0.03 per 10,000 population across the continent. The number of technicians also varies across the continent from 0.17 to.0.1 per 10,000 population. Southern Africa has the highest median dental assistants and therapists per 10,000 population ratio (0.2), whereas Northern Africa has no dental assistants or therapists. In addition, limited infrastructure and funding have resulted in significant oral health disparities, leaving large portions of the population without adequate access to oral health services. Only 57% of African countries have developed an oral health policy that sets targets and implementation strategies. African countries have also been shown to spend a fraction of their health budget on oral health care, albeit that dentistry is one of the most expensive medical services. Addressing these gaps requires addressing the oral health workforce needs, facilitating the development of oral health policies built on context-specific evidence, and guiding practice and policy. In addition, partnerships are needed to support innovation, sustainability and monitoring of the instituted oral health programs.